2021
DOI: 10.1038/s41598-021-87387-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G protein signaling 17 represents a novel target for treating cisplatin induced hearing loss

Abstract: Regulators of G protein signaling (RGS) accelerate the GTPase activity of G proteins to enable rapid termination of the signals triggered by G protein-coupled receptors (GPCRs). Activation of several GPCRs, including cannabinoid receptor 2 (CB2R) and adenosine A1 receptor (A1AR), protects against noise and drug-induced ototoxicity. One such drug, cisplatin, an anticancer agent used to treat various solid tumors, produces permanent hearing loss in experimental animals and in a high percentage of cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Subsequent studies have shown that other members of the RGS family of proteins may be involved in cisplatin-induced ototoxicity. Cisplatin upregulates RGS17 expression in the cochlea, leading to increased oxidative stress, upregulation of inflammatory genes and enhanced apoptosis in the cochlea [ 102 ]. The silencing of RGS17 suppressed cisplatin-induced hearing loss in rats, while overexpression of RGS17 enhanced cisplatin-induced hearing loss.…”
Section: Regulators Of G Protein Signalling and Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequent studies have shown that other members of the RGS family of proteins may be involved in cisplatin-induced ototoxicity. Cisplatin upregulates RGS17 expression in the cochlea, leading to increased oxidative stress, upregulation of inflammatory genes and enhanced apoptosis in the cochlea [ 102 ]. The silencing of RGS17 suppressed cisplatin-induced hearing loss in rats, while overexpression of RGS17 enhanced cisplatin-induced hearing loss.…”
Section: Regulators Of G Protein Signalling and Hearing Lossmentioning
confidence: 99%
“…The silencing of RGS17 suppressed cisplatin-induced hearing loss in rats, while overexpression of RGS17 enhanced cisplatin-induced hearing loss. RGS17 represents a novel mediator of cisplatin ototoxicity and a potential therapeutic target for cisplatin-induced hearing loss [ 102 ].…”
Section: Regulators Of G Protein Signalling and Hearing Lossmentioning
confidence: 99%
“…CB2Rs are mainly distributed in OC, spiral ligament and SGN cells in the cochlea of rats and mice ( Kim et al, 2014 ; Kaur et al, 2016 ; Ghosh et al, 2018 ). CB2Rs can protect the cochlea and reduce ototoxicity, inflammation and oxidative stress with cisplatin treatment in rats ( Vlajkovic et al, 2006 ; Dhukhwa et al, 2021 ). The effect of CB2Rs on preventing cisplatin induced hearing loss was blocked by injection of the antagonist AM630, but HC loss was reduced by injection of JWH105 (one agonist of CB2R).…”
Section: Roles Of Class a G Protein-coupled Receptors In Cochleamentioning
confidence: 99%
“…In cochlear research and treatment, GPCR-targeted drugs have also been used to some extent. For example, S1PR2 agonist (CYM-5478) ( Wang et al, 2020 ), CaSR inhibitors (NPS2143 and Calhex231) ( Minakata et al, 2019 ), V2R antagonist (OPC-41061/Tolvaptan) ( Egami et al, 2016 ), CB2R agonist (JWH105) ( Vlajkovic et al, 2006 ; Dhukhwa et al, 2021 ), AA1R agonists (R-PIA and ADAC) ( Vlajkovic et al, 2010 ; Kaur et al, 2016 ), AA2AR antagonist (istradefylline) ( Han et al, 2019 ; Manalo et al, 2020 ; Shin et al, 2021 ) all have a therapeutic and protective effect on the cochlea. Among these GPCR-targeted drugs, V2R antagonist (OPC-41061/Tolvaptan) and AA2AR antagonist (istradefylline) have been approved by the US Food and Drug Administration (FDA) (NDA022075, NDA022275).…”
Section: Emerging G Protein-coupled Receptor-based Treatmentmentioning
confidence: 99%
“…RGS 17 appears to contribute to cisplatin ototoxicity by uncoupling protective GPCRs, such as CB2, from their normal protective actions. RGS17 inhibitors could provide novel agents for ameliorating cisplatin induced hearing loss [ 71 ] by extending the period of activation of GPCR activation.…”
Section: G-proteinsmentioning
confidence: 99%